[6]-Shogaol Inhibits α-MSH-Induced Melanogenesis through the Acceleration of ERK and PI3K/Akt-Mediated MITF Degradation. (19th June 2014) - Huang, Huey-Chun; Chang, Shu-Jen; Wu, Chia-Yin; Ke, Hui-Ju; Chang, Tsong-Min
Abstract : [ 6 ] -Shogaol is the main biologically active component of ginger. Previous reports showed that [ 6 ] -shogaol has several pharmacological characteristics, such as antioxidative, anti-inflammatory, antimicrobial, and anticarcinogenic properties. However, the effects of [ 6 ] -shogaol on melanogenesis remain to be elucidated. The study aimed to evaluate the potential skin whitening mechanisms of [ 6 ] -shogaol. The effects of [ 6 ] -shogaol on cell viability, melanin content, tyrosinase activity, and the expression of the tyrosinase and microphthalmia-associated transcription factor (MITF) were measured. The results revealed that [ 6 ] -shogaol effectively suppresses tyrosinase activity and the amount of melanin and that those effects are more pronounced than those of arbutin. It was also found that [ 6 ] -shogaol decreased the protein expression levels of tyrosinase-related protein 1 (TRP-1) and microphthalmia-associated transcriptional factor (MITF). In addition, the MITF mRNA levels were also effectively decreased in the presence of 20 μ M [ 6 ] -shogaol. The degradation of MITF protein was inhibited by the MEK 1-inhibitor (U0126) or phosphatidylinositol-3-kinase inhibitor (PI3K inhibitor) (LY294002). Further immunofluorescence staining assay implied the involvement of the proteasome in the downregulation of MITF by [ 6 ] -shogaol. Our confocal assay results also confirmed that [ 6 ] -shogaol inhibited α -melanocyte stimulating hormone- ( α -MSH-) induced melanogenesis through the acceleration of extracellular responsive kinase (ERK) and phosphatidylinositol-3-kinase- (PI3K/Akt-) mediated MITF degradation.